Panorama epidemiology of dengue in the city of Ariquemes, Rondonia, Western Amazon, 2002-2011. - Rodrigo de Almeida Borges; Leandro José Ramos; Renato André Zan; Naila Fernanda Sbsczk Pereira Meneguetti; Dionatas Ulises de Oliveira Meneguetti (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: The present study aimed to evaluate the incidence and frequency of dengue in the city of Ariquemes - Rondônia (RO), occurred in the period 2002-2011. Method: Indirect research in database of public domain unrestricted access. The base used (Sinan-Net), being researched the number of cases investigated their age distribution and seasonality, and calculating the incidence rate and the risks related. Results: Has reported a prevalence of 2007 confirmed cases, with higher incidence in 2005 and 2009. It was evident that the higher occurrence of cases occurs in the months of greatest rainfall from January to March in all the months most affected age group was 20-34 years, and female gender. Conclusion: Dengue epidemics occurred in the city of Ariquemes, comes not only social, but also due to the emergence of new serotypes. KEYWORDS: Epidemiologia. Dengue. Flavivírus.